Screen Time vs. Quality Time: The 21st Century Battle in Raising Children - KHAIDIR FADIL; Nurus Sa'adah; Reni Sinta Dewi; Rusdi Kasman; Adi Abdurrahman (Department of Guidance and Counseling, FIP, Undiksha, 2025)
The increasing imbalance between children’s screen time and family quality time has become a major parenting challenge in the digital era, affecting children’s social, emotional, and mental health development. This study aims to analyze the implications of screen time and quality time on parent–child relationships and to identify digital parenting strategies to balance both. The type of research used is qualitative with a library research approach. The research subjects consist of scientific literature published in reputable journals, academic books, and official documents from international education and health organizations. Data was collected through documentation techniques using a literature review instrument validated by experts. Data analysis was conducted using content analysis and thematic analysis approaches. The research findings indicate that excessive screen time has a negative impact on the quality of parent-child relationships, emotional regulation, and children's social skills. Conversely, well-managed quality time has been proven to strengthen family emotional bonding and prevent relational dysfunction. Parental digital mediation strategies such as co-viewing, active mediation, and value-based restrictions have been proven effective in reducing the negative impacts of digital media. This study concludes that the balance between screen time and quality time needs to be consciously managed by parents. Implications include the need for family education policies and value-based digital parenting training within the local cultural context.